EFEK APLIKASI PENDEKATAN BERMAIN TERHADAP KEMAMPUAN PASSING MENYUSUR TANAH - Ikhsan Fajar Kurniawan; Budhi Satyawan (PHEDHERAL, 2017)
This research aims to determine the effectiveness of the effects of applications using playing approach to the ability of passing along the ground on the football school AD Batik Surakarta age group 13-14 years old, and a better approach effect between playing approach and technique approach to the ability of passing along the ground on the football school AD Batik Surakarta age 13-14 years old.The research subjects in this research are students of the football school AD Batik Surakarta age group 13-14 years old with the number of 30 students. The method which is used is Quasi Experimental Research (QER) conducted with pretest-posttest design Matching Comparrison Control Group Design. The technique of data collection in this research is testing and measurement capabilities passing along the ground. The data analysis technique used is inferential statistical analysis.The results of this research are as follows, first, the playing approach application gives an effect on the ability of passing along the ground on the football school AD Batik Surakarta age group 13-14 years whichcan be seen from the comparison inferentially increases from 30.5% (without variable covariates ) to 76.2% (with variable covariate). Second, the playing approach application has a better effect than a technical approach to the ability of passing along the ground on a football school AD Batik Surakarta age group 13-14 years old. Based on the percentage of the increasing of the ability of passing along the ground shows that the experimental group (the group treated with the playing approach ) is 72.7% greater than the control group (the group which treated with technique approach) is 31.1%.The conclusion of the research is the application using playing approach gives the effect to ability of the passing along the ground and the application using playing approach has a better efect than the technique approach to the ability of passing along the ground on the football school AD Batik Surakarta age 13-14 years old.